The impact of digital rural construction on agricultural carbon emission intensity - Li, Weijuan; Guo, Jinyong; Tang, Yonghong; Zhang, Pengcheng (Frontiers in Environmental Science, 2024)
Reducing agricultural carbon emissions is critical to achieving green agricultural development and the “dual carbon” goals. The present study conducts empirical analysis using provincial panel data from 29 provinces in China from 2011 to 2022 combined with econometric models based on the mechanism of the impact of digital rural construction on agricultural carbon emission intensity. The entropy method and carbon emission factor method are used to determine the level of digital rural construction and agricultural carbon emission intensity. The fixed effect and intermediary effect models are used to empirically analyze the impact of digital rural construction on agricultural carbon emission intensity. The results indicate that (1) digital rural construction significantly inhibits agricultural carbon emission intensity, and there are differences in different regions and dimensions of digital rural construction; (2) the construction of digital rural areas can indirectly reduce the intensity of agricultural carbon emissions by promoting the level of rural human capital; (3) financial support for agriculture played significant positive regulatory effect. The policy recommendations are proposed to provide a reference for promoting agricultural carbon reduction and digital rural construction in other countries.